Convergence of Dermoscopic and Histopathological Findings in Diagnosing Cutaneous Lichen Planus (CLP) - Sumera Hanif; Tariq Rashid; Muhammad Talha Farooq; Mahrukh Javaid; Areesha Fatima; Bushra Hassan; Muhammad Umair Iqbal; Amina Akram (BioScientific Review, 2022)
Lichen planus (LP) is an immune mediated disorder that is usually diagnosed clinically. Dermoscopy is a non-invasive diagnostic technique. It can act as an alternative technique to skin biopsy that remains the gold standard for the diagnosis of the disease. The current study aimed to evaluate the degree of convergence between dermoscopy and histopathology in diagnosing LP. It is a cross-sectional study conducted at Jinnah Hospital, Lahore for six (6) months. Sixty (60) patients who met the inclusion criteria were recorded. After taking their informed consent and detailed history, clinical examination and relevant investigations were carried out and recorded in a pre-structured proforma. All patients were subjected to dermoscopic examination. A total of 4 mm punch biopsy were taken from the same site for histopathological examination and sent to JHL Histopathology lab. The results of dermoscopic and histopathological examinations were recorded. Effect of modifiers such as age, gender, and duration of disease were addressed through the stratification of data.Data was analyzed using SPSS 23. The mean age of subjects was 35 years. Of the total 60 patients, 56.6% were female and 43.3% were male. Among the subjects, 94.7% cases diagnosed on histopathology were also diagnosed on dermoscopy, while 5.3% cases were not diagnosed on dermoscopy. Kappa statistics showed a substantial convergence between the two diagnostic modalities: (X2=29.697, p=.000) and (k= .700, p =.000). It was determined that dermoscopy is as effective as hitopathology in the diagnosis of CLP.